Transmission electron microscopy of the vitreomacular border in clinically significant diabetic macular oedema - Synek, Svatopluk; Páč, Libor; Synková, Monika (Scripta medica Facultatis medicae Universitatis Brunensis Masarykianae, 2008)
Diabetic cystoid macular oedema (DME) is a common cause of visual acuity decrease. Good anatomical results and visual acuity (VA) of pars plana vitrectomy (PPV) in a case of a macular hole with internal limiting membrane peeling leads to the use of this technique in DME. A favourable result even in a case without vitreoretinal traction leads to the conclusion that pathogenesis of this disease is different. We analysed retrospectively 20 eyes from 20 patients with DME that had undergone PPV and peeling ILM. Half of them were laser treated before surgery. All eyes had an attached posterior hyaloid membrane in the macular region, but without thickening and without traction. We examined parts of excised tissues by transmission electron microscopy (TEM). Median duration of DME at the time of PPV was approximately 18.0 months (range 12 – 24 months). The median preoperative best corrected VA of 0.4 (range 0, 01–1, 0), improved to a median postoperative VA of 0.55 (range 0, 01–1, 0). Ten eyes without preoperative laser coagulation had a median VA improvement of 112 %, while 10 eyes with preoperative focal macular laser treatment had a median VA improvement of 17 %. In all 20 eyes, DME was no longer visible on microscopic examination after a median period of 3.0 months after PPV. We classified TEM samples containing ILM, glial cells and connective tissue as monolayer membrane, multilayer membrane, and true epimacular fibrous membrane. PPV and peeling ILM resulted in the resolution of oedema, with an improvement in visual acuity in the majority of cases. Eyes without preoperative macular photocoagulation had a significantly higher visual improvement than eyes with preoperative laser treatment, but PPV had an additive effect on final visual acuity in focal laser treated eyes. A randomised controlled prospective trial of PPV versus laser is needed to determine the role of PPV as a treatment modality for DME.
Keywords: Vitrectomy; mikroskopie elektronová rastrovací transmisní; financování organizované; Diabetes Complications; Microscopy, Electron, Scanning Transmission; Statistics as Topic; Financing, Organized; lidé; makulární edém; prospektivní studie; Diabetic Retinopathy; vitrektomie; komplikace diabetu; diabetická retinopatie; statistika jako téma; Prospective Studies; Macular Edema; Humans